Exact Solutions for Minimizing cost Function with Five Criteria and Release Dates on Single Machine - Chachan, Hanan Ali; Jaafar, Hussein Abdullah (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
In this paper, we present a Branch and Bound (B&B) algorithm of scheduling (n) jobs on a single machine to minimize the sum total completion time, total tardiness, total earliness, number of tardy jobs and total late work with unequal release dates. We proposed six heuristic methods for account upper bound. Also to obtain lower bound (LB) to this problem we modified a (LB) select from literature, with (Moore algorithm and Lawler’s algorithm). And some dominance rules were suggested. Also, two special cases were derived. Computational experience showed the proposed (B&B) algorithm was effective in solving problems with up to (16) jobs, also the upper bounds and the lower bound were effective in restricting the search.